Do saproxylic beetles respond numerically to rapid changes in dead wood availability following moth outbreaks? - Schultze, Sabrina (Universitetet i Tromsø, 2012)
Outbreaks of defoliating insects periodically cause mass mortality of trees, thereby generating pulses of dead wood resources for saproxylic (i.e. dead-wood dependent) organisms. This study investigated the responses of saproxylic beetles to a dead wood resource pulse caused by recent (2001-2009) outbreaks of geometrid moths in the subarctic mountain birch forest of the Varanger region in northern Norway. A large scale (20 km) transect design, implementing window (flight interception) traps and replicated in two areas, was used to compare beetle community structure between outbreak (dead wood) and non-outbreak (live wood) locations. The overall abundance and species richness of saproxylic beetles did not differ consistently between live- and dead wood sections of the transects. However, the two most common early successional saproxylic species, Hylecoetus dermestoides and Rabocerus foveolatus, were significantly more abundant in the dead wood sections of both transects, while no such responses were found in later successional saproxylic species. With respect to trophic groups, mycetophagous beetles were significantly more abundant in dead wood, but this response was entirely driven by H. dermestoides. Moreover, carnivorous beetles strongly dominated the beetle community along the entire transects, regardless of wood vitality. The lack of an overall response from saproxylic beetles to dead-wood-availability, combined with the raised abundance of a few early successional species, suggests that four to eight years after the moth outbreaks saproxylic beetle succession in the Varanger region is still in an initial phase.